Indonesia and China : the politics of a troubled relationship - Sukma, Rizal, 1964- (Politics in Asia series., 1999)
Indonesia broke off relations with China in 1967 and resumed them only in 1990. Rizal Sukma asks why. His answers shed light on Indonesia's foreign policy, the nature of the New Order's domestic politics, the mixed functions of diplomatic ties, the legitimacy of the new regime, and the role of President Suharto. Rizal Sukma argues that the matter of Indonesia restoring diplomatic ties with China is best understood in terms of the efforts made by the military-based New Order government to sustain its political legitimacy. The analysis in this book proves that an absence as well as a presence o.